ABREVIASI, AFIKSASI, DAN REDUPLIKASI RAGAM BAHASA REMAJA DALAM MEDIA SOSIAL FACEBOOK - Domas Sugrahita Harja Susetya (UNZAH Genggong, 2020)
The use of various youth languages ​​is intended to create a group identity that is separate from other groups. The purpose of this research is to explain the abbreviation, affixation, and reduplication in the various languages ​​of adolescents on social media Facebook and mention the factors that influence the use of abbreviations, affixations, and reduplications in the various languages ​​of adolescents on social media Facebook. The method in this research is descriptive method. The approach in this research is qualitative. With this approach, data is collected and presented in words. The data in this study are written language in the form of lingual units found on the Facebook account. The data collection technique in this research is to collect secondary data. The data was taken randomly from January 2013 to April 2013, from 100 (one hundred) posts on Facebook which contained morphological process data in the form of abbreviation, affixation, and reduplication by upholding the principles of confidentiality and keeping respondents private. The data will be described and classified based on abbreviation, affixation, and reduplication in the various languages ​​of adolescents on social media Facebook and the factors that influence the use of abbreviations, affixations, and reduplications in various juvenile languages ​​on Facebook social media. Data analysis techniques are data reduction, researching morphological processes, classifying based on abbreviation, affixation and reduplication, data display, verification, and conclusions. The factors in the emergence of this morphological process include teenagers expressing self-expression, building a different identity, making the social atmosphere feel more